2015
DOI: 10.1007/s13277-015-3137-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-enzymatic action of RRM1 protein upregulates PTEN leading to inhibition of colorectal cancer metastasis

Abstract: Ribonucleotide reductase large subunit M1 (RRM1) forms a holoenzyme with small subunits to provide deoxyribonucleotides for DNA synthesis and cell proliferation. Here, we reported a non-RR role of the catalytic subunit protein RRM1 and related pathway in inhibiting colorectal cancer (CRC) metastasis. Ectopic overexpression of the wild-type RRM1, and importantly, its Y738F mutant that lacks RR enzymatic activity, prevented the migration and invasion of CRC cells by promoting phosphatase and tensin homolog on ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Therefore, the well-differentiated thyroid carcinoma cell line TPC-1 and the poor-differentiated thyroid carcinoma cell line SW579 were employed to assess the effect of RRM1 expression on the malignant behaviors of TC. The results of cell viability and EdU incorporation assays showed that RRM1 contributed to the DNA synthesis and proliferation in the both cell lines, which was consistent with previous studies in other cancers [12,13]. However, wound healing and transwell assays in this study showed that RRM1 enhanced the migration and invasion of TPC-1 cells but inhibited that in SW579 cells.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, the well-differentiated thyroid carcinoma cell line TPC-1 and the poor-differentiated thyroid carcinoma cell line SW579 were employed to assess the effect of RRM1 expression on the malignant behaviors of TC. The results of cell viability and EdU incorporation assays showed that RRM1 contributed to the DNA synthesis and proliferation in the both cell lines, which was consistent with previous studies in other cancers [12,13]. However, wound healing and transwell assays in this study showed that RRM1 enhanced the migration and invasion of TPC-1 cells but inhibited that in SW579 cells.…”
Section: Discussionsupporting
confidence: 92%
“…High expression of RRM1 was predictive of long survival in NSCLC [17]. For the possible mechanism of RRM1 in suppressing cancer progression, previous studies reported that RRM1 can reduce the level of phosphorylated Akt and increase the expression of E-cadherin by promoting the transactivation of PTEN, which result in the inhibition of cancer migration, invasion, and metastasis [12,16], which is consistent with our results that RRM1 promoted PTEN expression and reduced Akt phosphorylation in low- Especially, we previously demonstrated that the tumor suppressor role of RRM1 in colorectal cancer may be attributed to its non-RR function by biological analyses using a RRM1 mutant that lacks catalytic activity, and our further clinical specimen examinations demonstrated that RRM1 protein level was significantly increased at stages T1-3 but decreased at stage T4, in parallel with the PTEN expression level and negatively correlated with invasion and liver metastasis [12]. Thus, combined with our TC data in this study, we propose that RRM1 contributes to DNA synthesis and cell proliferation in cancers.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The specific activity of the C779S, C787S, and C790S mutants was about 6.0, 0.3, and 1.3% of that of the wild-type RRM1, respectively, suggesting a critical role of Cys 779 in RRM1 reduction by hTrx1, although it may be less important than Cys 787 and Cys 790 . It is known that ectopic expression of RRM1 (wild type) increases RR enzymatic activity and cell proliferation in CRC cells, whereas the RR-inactive mutant RRM1-Y738F fails to provide deoxyribonucleoside diphosphates, thus blocking DNA synthesis and cell proliferation in the transfected CRC cells (9). As shown in supplemental Fig.…”
Section: In Addition To the Known Cys 787 And Cys 790 A Novel Cystementioning
confidence: 94%